Agents, Institutions, and French Empire/State Formation - Dewar, Helen (The Canadian Historical Review, 2021)
This article explores the ways in which historians of New France are engaging with Atlantic, imperial, and comparative frameworks, as well as theoretical literature to better understand big historical processes such as state and empire formation and sovereignty. It also shows how traditional categories separating political, economic, social, and religious phenomena are breaking down, allowing for a deeper understanding of the ways in which their interactions shaped French imperial expansion. Empire formation depended on both agents and institutions. Going beyond the traditionally narrow conceptions of each, the article examines the widening range of actors who are now considered agents of empire as well as the recent move beyond Church and state to consider other institutions, notably the understudied chartered company. The latter is particularly fruitful for rethinking the relationship among traditionally separate groups of actors and institutions. Resituating the Company of New France in Atlantic, imperial, and comparative frameworks highlights the complex intertwining of religious, political, economic, and social phenomena that was at the heart of French imperialism. The article closes with a brief discussion of the parallels to nineteenth-century railroad corporations and their relationship with the state to highlight the evolving dynamic between states and corporations in a broader chronology. Finally, a number of avenues are proposed for future research into that relationship, for which New France and the French empire are particularly rich sites of inquiry.
Keywords: Atlantique français; French Atlantic; New France; Nouvelle-France; chartered company; compagnie à charte; corporation; empire formation; entreprise; formation d’un empire; souveraineté; sovereignty